Large-Scale Label-Free Comparative Proteomics Analysis of Polo-Like Kinase 1 Inhibition via the Small-Molecule Inhibitor BI 6727 (Volasertib) in BRAF(V600E) Mutant Melanoma Cells - Cholewa, Brian D. (J Proteome Res, 2014)
[Image: see text] Polo-like kinase 1 (Plk1) is a serine/threonine kinase that plays a key role during the cell cycle by regulating mitotic entry, progression, and exit. Plk1 is overexpressed in a variety of human cancers and is essential to sustained oncogenic proliferation, thus making Plk1 an attractive therapeutic target. However, the clinical efficacy of Plk1 inhibition has not emulated the preclinical success, stressing an urgent need for a better understanding of Plk1 signaling. This study addresses that need by utilizing a quantitative proteomics strategy to compare the proteome of BRAF(V600E) mutant melanoma cells following treatment with the Plk1-specific inhibitor BI 6727. Employing label-free nano-LC–MS/MS technology on a Q-exactive followed by SIEVE processing, we identified more than 20 proteins of interest, many of which have not been previously associated with Plk1 signaling. Here we report the down-regulation of multiple metabolic proteins with an associated decrease in cellular metabolism, as assessed by lactate and NAD levels. Furthermore, we have also identified the down-regulation of multiple proteasomal subunits, resulting in a significant decrease in 20S proteasome activity. Additionally, we have identified a novel association between Plk1 and p53 through heterogeneous ribonucleoprotein C1/C2 (hnRNPC), thus providing valuable insight into Plk1’s role in cancer cell survival.